(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: There is a realization that learning leadership skills is beyond classroom teaching and requires leaders to participate in communities of practice (CoP) that enables them to learn from the wisdom of seasoned leader because such leaders don’t ask budding leaders to follow their instructions, they rather set examples of best practices in medical education. However, dearth of published evidence both locally and internationally suggests that there is a need to investigate how have communicates of practice impacted leadership skills of physicians as medical education leaders. Participants and Methods: A transcendental phenomenological study was conducted, involving seven physician leaders working as medical teachers from both basic and clinical sciences, heading the medical college and/or their departments as professors in a medical college on the basis of convenience sampling and their experiences as medical education leaders who had presumably experienced the phenomenon of ‘learning leadership skills’. The researcher conducted hour-long one-on-one interviews with participants at their workplace offices and one interview was conducted at the researcher’s home office. One of the participants was interviewed twice as additional gaps were identified from the initial analysis. Interviews conducted in the surgeon’s office were interrupted many a times by theatre assistants, but the continuity was resumed successfully. The qualitative data was analyzed manually by using the Stevick-Colaizzi-Keen method. Results: One major theme namely ‘communities of practice impacting leadership skills’ emerged from the transcripts whereas, two subthemes namely ‘gaining wisdom’ and ‘uplifting emotional wellbeing’ were identified as main aspects that had a major influence on leadership skills of physicians in the medical education milieu. Conclusion: CoP has a positive impact on leadership skills. It enables leaders in medical education to learn wisdom to solve difficult leadership problems. Evidence supports that CoP also uplifts emotional wellbeing of leaders by preventing their burn out.